STUDENTS’ PERCEPTIONS OF ENGLISH LEARNING MATERIALS FOR CHILDHOOD EDUCATION THROUGH PJBL MODEL - Fera Zasrianita; Syukri Hamzah; Andriadi Andriadi; Nadrah Nadrah (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study aims to understand the students' perceptions towards the implementation of English language material for early childhood based on project-based learning. This research was a qualitative descriptive study. The method used in this research is the survey method. The subject of this study was a student of the 6th semester at English Language Education who took TEYL courses at FTT UIN FAS Bengkulu. There were 26 (twenty-six) students in the sample for the research. In collecting the data, the researcher used a questionnaire about students' perceptions towards the implementation of project-based learning in designing English learning material for early childhood education. The result of the research clearly showed that project-based learning has a significant impact on student performance in designing English learning material for early childhood education. In designing English learning material for early childhood education. The subject of this study was a student of the 6th semester at English Language Education who took TEYL. There were 26 students in the sample for the research. In collecting the data, the researcher used a questionnaire about students' perceptions towards the implementation of project-based learning in designing English learning material for early childhood education. The result of the research clearly showed that project-based learning has a significant impact on student performance in designing English learning material for early childhood education.